2011
DOI: 10.2147/ndt.s13917
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for the development of depression in patients with hepatitis C taking interferon-α

Abstract: Interferon-α, currently used for the treatment of hepatitis C, is associated with a substantially elevated risk of depression. However, not everyone who takes this drug becomes depressed, so it is important to understand what particular factors may make some individuals more ‘at risk’ of developing depression than others. Currently there is no consensus as to why interferon-induced depression occurs and the range of putative risk factors is wide and diverse. The identification of risk factors prior to treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
29
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 137 publications
(208 reference statements)
3
29
1
3
Order By: Relevance
“…Therefore, identification of the risk factors for the subsequent development of depression in HCV patients is necessary (28). Yet, physicians must consider the risk of depression particularly in the patients with a current or past history of depression, other psychiatric diseases, hospitalization for any psychiatric diseases, and suicide attempts before stating the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, identification of the risk factors for the subsequent development of depression in HCV patients is necessary (28). Yet, physicians must consider the risk of depression particularly in the patients with a current or past history of depression, other psychiatric diseases, hospitalization for any psychiatric diseases, and suicide attempts before stating the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Negative cognitions are a key part of the depressive syndrome, 8 but are not a feature of sickness behavior. 9,10 The fact that IFN-a did not increase negative cognitions in this sample indicates that the behavioral syndrome we observed is due to sickness behaviors and could be different to an idiopathic depression. Support for this idea comes from the work of Pasquini et al 17 who found that an IFN-a-induced depression comprised significantly less negative cognitions than a primary depression.…”
Section: Discussionmentioning
confidence: 70%
“…8 Many of the symptoms of MDD are also the features of sickness behaviors, 9,10 with the main difference between these two syndromes being the presence of negative cognitions such as hopelessness, helplessness and worthlessness in MDD but not sickness behavior. The observation that sickness behaviors overlap considerably with symptoms of MDD has led to considerable interest in trying to understand the behavioral syndrome that accompanies IFN-a therapy.…”
mentioning
confidence: 99%
“…The present work focuses on opioid receptor modulators in dysregulated motivational and stress coping behavior [13,14], using the clinically-relevant, back-translational, rat interferonalpha (IFN-α) depression model [15][16][17][18][19]. We employed a progressive ratio (PR) task reinforced with a natural reward (sucrose pellets) to examine motivated behavior, and the FST to assess stress-coping behavior.…”
Section: Introductionmentioning
confidence: 99%